Ground Level Ozone Fluctuational Characteristics from a Background Station of Malaysia - Hasifah Abdul Aziz, Norrimi Rosaida Awang; Mohamad Faiz Mohd Amin (International Journal of Advanced Science and Technology, 2020)
The fluctuational of ground level ozone (GLO) were investigated (year 2000 to 2011) in a rural site located in the central region of Peninsula Malaysia, far from direct sources of anthropogenic emissions. This study aims to analyse the fluctuation and transformation characteristics of GLO in rural area of Jerantut, Pahang. By using Critical Conversion Point and Time (CCP and CCT) and Critical Transformation Time (CTT) obtained from composite diurnal plot. CTT is important to understand the different processes responsible for GLO transformation. The CCT for ozone formation at Jerantut was identified occurring between 8.00 a.m. to 9.00 a.m. Jerantut hourly continuous monitoring recorded data was below 100 part per billion volume (ppbv). CTT fluctuational characteristics at the background station is important and provide an early signal to developed policies that manage nitrogen emission from background station that free from rapid development projects.